Energy distribution modelling in the weld zone for various electron beam current values in COMSOL Multiphysics. Issue 4 (April 2021) - Tynchenko, V S; Kurashkin, S O; Murygin, A V; Tynchenko, Ya A
Abstract: The presented work is devoted to the study of the effect of various values of the electron beam current on the distribution of the energy cross section of the weld when conducting the technological process of electron-beam welding of thin-walled structures. The work is used by the simulation system of COMSOL Multiphysics, in which mathematical models of energy distribution proposed by the authors are implemented with electron beam welding. Imitation modelling was carried out for two materials widely used in the aerospace industry: titan alloy BT14 and AMG aluminum alloy. The values of the parameters for which the simulation was carried out were selected as a result of the predetermined process of optimizing the technological mode of electron beam welding for the construction under study. In the process of the research, a change in the value of the electron beam current is carried out both in less and to the large side. The article presents visualization for the three values of the parameter under study for each material, which makes it possible to judge the effectiveness of the previously formed set of optimal parameter values.